Predicting Imaging Remission in Rheumatoid Arthritis: a Case-control Ultrasound Study - Chung, Sang Wan (J Korean Med Sci, 2020)
BACKGROUND: To elucidate the achievement rates of imaging remission and to examine the characteristics associated with imaging remission status among patients with rheumatoid arthritis (RA) who have attained clinical remission. METHODS: Ninety-seven patients with RA patients who had attained clinical remission, defined by DAS28-ESR < 2.6 were enrolled. Power Doppler ultrasonography (PDUS) was performed on 16 joints and 2 tendons, including the first to third metacarpophalangeal, second and third proximal interphalangeal, radiocarpal (RC), second and third metatarsophalangeal joints, and extensor carpi ulnaris tendons. They were graded based on a dichotomous assessment. The clinical and laboratory data of patients who had attained imaging remission were compared to those of patients who had attained only clinical remission. RESULTS: The imaging remission rate was 51.5% in patients who had attained clinical remission. Forty-seven patients (48.5%) were PDUS positive. Power Doppler was detected most frequently in the right RC joint (n = 40). PDUS positive patients had higher evaluator global assessment (EGA) scores (P < 0.001) than PDUS negative patients. PDUS positive patients also had higher clinical disease activity index and simplified clinical disease activity index scores than PDUS negative patients. Patients who had attained imaging remission had lower pain scores and used nonsteroidal anti-inflammatory drugs less frequently. Patients who had attained imaging remission had higher rheumatoid factor (RF) and anti-cyclic citrullinated peptide levels. A low EGA score was found to be a predictor of imaging remission achievement among patients who had attained clinical remission. CONCLUSION: Only 51.5% of the patients with RA who had attained clinical remission were also in imaging remission. Patients who had attained imaging remission had lower EGA scores and higher RF levels than patients who had attained only clinical remission.